Infection of water buffalo in Rio de Janeiro Brazil with Anaplasma marginale strains also reported in cattle - Silva, Jenevaldo B. [UNESP]; Cabezas-Cruz, Alejandro; Fonseca, Adivaldo H.; Barbosa, Jose D.; la Fuente, Jose de (Elsevier B.V., 2014)
Anaplasma marginale is the most prevalent pathogen of cattle in tropical and subtropical regions of the world and causes the disease bovine anaplasmosis. The importance of water buffalo in the world economy is increasing. In addition, while water buffalo may serve as a reservoir host for A. marginale, the susceptibility of this host for A. marginale cattle strains in Brazil has not been reported. The major surface protein 1 alpha (msp1 alpha) gene has been shown to be a stable genetic marker for identification of A. marginale strains. Herein, we analyzed blood samples from 200 water buffalo and identified the A. marginale strains in an endemic area of Rio de Janeiro, Brazil, where ticks were present and water buffalo and cattle co-mingled. Ticks that were feeding on the study buffalo were collected and identified. The prevalence of A. marginale in water buffalo in this study was low (10%). Sequence analysis of the msp1 alpha gene demonstrated the presence of 8 different A. marginale strains. Two A. marginale strains in the water buffalo, (alpha-beta-beta-beta-Gamma) and (alpha-beta-beta-Gamma), were similar to those reported in cattle from nearby regions. The results of this study suggested that water buffalo in this region are naturally infected with the same strains of A. marginale found in cattle. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Water buffalo; Bovine anaplasmosis; Anaplasma marginale; msp1 alpha; Ticks